Seed Quality Status in Groundnut (Arachis hypogea L.) - RAJENDRA KUMAR; S.S. PARIHAR; I. JETHANI; H.C.S. NEGI (Seed Research, 2026)
This paper gives an account of seed quality parameters of 140 seed samples of groundnut tested in the Central Seed Testing Laboratory under Collaborative Seed Testing programme with State Seed Testing Laboratories. Detailed examination of seedlings was done in order to distinguish critically those which have the potential to produce the normal plants (normal seedlings) from those, which are without planting value (abnormal seedlings). All the seed samples showed more than 70% germination i.e. normal seedlings (above the Minimum Seed Certification Standard), except two. Seed quality in respect of its storability and quality of farmer’s own saved seeds is also being discussed.